Effects of fermentation on the crude protein, calcium content, and iron content of fermented malunngay (Moringa oleifera Lam.) juice - Toledo, Rebecca Mae A.
There is an increasing interest in practicing natural farming using fermented plant juice as soil enhancersand consuming them as herbal drink, which emphasizes the need to conduct scientific studies on its production.